DESAIN LKPD FISIKA BERORIENTASI AL-QUR’AN DENGAN STRATEGI INKUIRI TERBIMBING TERHADAP PENCAPAIAN KOMPETENSI PESERTA DIDIK SMA/MA - Chandra, Artha Nesa; Haryati, Siti; Haris, Venny (IAIN Batusangkar, 2020)
Mostly, teaching materials merely focus on formulas and theories, yet there has not been found any teaching materials oriented to Qur'an. Due to that reason, it is significant to provide materials enabling students to learn independently, especially, those correlating the physics materials with Qur'an. Therefore, this study aimed to produce students' worksheets of physics, known as LKPD, correlating Qur?an with Guided Inquiry to achieve the students? competencies, particularly, in the topic of equilibrium and rotational dynamics. This study employed the Research and Development design with the 4-D research model consisting of four stages, namely defining, designing, developing, and disseminating. This LKPD also contains six stages of Guided Inquiry, namely orientation, formulating problems, formulating hypotheses, collecting data, testing hypotheses, and formulating conclusions. Every stage of Guided Inquiry engages the Qur?an verses with the material. The findings showed the validity of LKPD was at 88% categorized as very valid. The questionnaires resulted 88% of teachers and 70.3% of students categorized as very practical and practical. The average post-test score for students? competence (82.45) is higher than the average pre-test score (49.64) and N-gain of 0.77 considered high and effective. In conclusion, the physics students' worksheet or LKPD which employed Guided Inquiry corresponding with Qur?an is considered valid, practical, and effective to promote students in learning physics.